SLOW VIOLENCE AGAINST WOMEN IN THE MEXICAN HOSPITALITY SECTOR - Reyes-Santiago, María del Rosario; Sánchez-Medina, Patricia S. (Veredas do Direito, 2025)
The main objective of this research is to visualize different scenarios of violence against women working in the Mexican hospitality sector. On the theoretical side, this paper delves into a gender-based approach to slow violence that hinders access to the sector’s social sustainability. Methodologically, secondary data was analyzed using economic censuses from 2003 to 2018. The sample included all 32 states of the Mexican Republic. Based on the collected data, descriptive and inferential statistical tools were used to present an overview of the main tourism-related variables and a map identifying tourist regions with varying scenarios of violence against women. The results show that women working in the hospitality sector are exposed to various forms of slow violence, both within the industry and in the surrounding environment.